A study of the molecular mechanism of binding kinetics and long residence times of human CCR5 receptor small molecule allosteric ligands. (July 2014) - Swinney, David C; Beavis, Paul; Chuang, Kai‐Ting; Zheng, Yue; Lee, Ina; Gee, Peter; Deval, Jerome; Rotstein, David M; Dioszegi, Marianna; Ravendran, Palani; Zhang, Jun; Sankuratri, Surya; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose The human CCR5 receptor is a co‐receptor for HIV‐1 infection and a target for anti‐viral therapy. A greater understanding of the binding kinetics of small molecule allosteric ligand interactions with CCR5 will lead to a better understanding of the binding process and may help discover new molecules that avoid resistance. Experimental Approach Using [3H] maraviroc as a radioligand, a number of different binding protocols were employed in conjunction with simulations to determine rate constants, kinetic mechanism and mutant kinetic fingerprints for wild‐type and mutant human CCR5 with maraviroc, aplaviroc and vicriviroc. Key Results Kinetic characterization of maraviroc binding to the wild‐type CCR5 was consistent with a two‐step kinetic mechanism that involved an initial receptor–ligand complex (RA), which transitioned to a more stable complex, R'A, with at least a 13‐fold increase in affinity. The dissociation rate from R'A, k−2, was 1.2 × 10−3 min−1. The maraviroc time‐dependent transition was influenced by F85L, W86A, Y108A, I198A and Y251A mutations of CCR5. Conclusions and Implications The interaction between maraviroc and CCR5 proceeded according to a multi‐step kinetic mechanism, whereby initial mass action binding and later reorganizations of the initial maraviroc–receptor complex lead to a complex with longer residence time. Site‐directed mutagenesis identified a kinetic fingerprint of residues that affected the binding kinetics, leading to the conclusion that allosteric ligand binding to CCR5 involved the rearrangement of the binding site in a manner specific to each allosteric ligand.